(untitled) (Baghdad Science Journal, 2005)
The breakfast key components of good nutrition and a large proportion of pupils to Ataatnol her breakfast at home and increase the failure rate breakfast increase the child’s age research aims to study the importance of breakfast and emphasize the need to contain aggregates of basic food and its relationship to the curriculum daily diet and its impact on the balance of proteins, fats in food daily as well as the effect of some relevant factors such as the mother’s level of education and the number of family members and summarized the most important results in that the percentage of 15.6% Neglected children eating breakfast as well as afternoon that Almaah percentages of calories coming from protein and fat at breakfast .....